COLORECTAL CANCER AND ITS RISK FACTORS AMONG PATIENTS ATTENDING A TERTIARY CARE HOSPITAL IN SOUTHERN KARNATAKA, INDIA - Aithal, Rashmi R; Shetty, Ranjitha S; S, Binu V; Mallya, Sneha Deepak; Shenoy K, Rajgopal; Nair, Suma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To determine the association between certain socio-demographic and life style factors with colorectal cancer. Methods: This case-control study was conducted using a pre-designed questionnaire among 100 incident colorectal cancer patients and 200 unmatched controls attending a tertiary care hospital in southern Karnataka. Cases and the controls were interviewed and details regarding their socio-demographic factors were collected. Information on lifestyle factors such as dietary habits, physical activity levels and substance use were documented. They were also assessed for presence of existing co-morbidities and family history of colorectal and other cancers. Multivariable logistic regression was performed to determine the association between various risk factors and colorectal cancer. Results: In the present hospital based study, mean age of the participants was less than 55 years. Sixty three percent of the cases and 54.5% of the controls were males. On multivariable analysis age â‰¥50years (OR=1.87; 95%CI=1.02-3.45), low physical activity (OR=5.66; 95%CI=3.10-10.34) and low frequency of fruits consumption (OR=4.10; 95%CI=2.21-7.50) and hypertension (OR= 4.65; 95% CI=1.32-16.44) showed a positive association with colorectal cancer. Conclusion: Promoting healthy dietary practices and physical activity among the middle aged population appears to be significant in the context of colorectal cancer prevention in the Indian subcontinent. Keywords: Colorectal cancer, Caseâ€“control, Risk factors, Lifestyle, Comorbidities.